THE IMPACT OF SELF-ASSESSMENT AND PEER ASSESSMENT ON LINGUISTIC DEVELOPMENT IN ENGLISH LANGUAGE LEARNING - Xusanova , Moxira (Scientific practical conference, 2025)
This article examines the significant role of self-assessment and peer assessment as formative evaluation strategies in fostering linguistic development among English language learners. Moving beyond traditional teacher-centric models, the paper argues that these metacognitive practices enhance learner autonomy, metacognitive awareness, and intrinsic motivation, leading to more profound and sustainable acquisition of linguistic competencies. The theoretical foundations are explored, drawing on sociocultural theory and metacognitive frameworks. Practical implications for classroom implementation are discussed, alongside an analysis of potential challenges and strategies to mitigate them. The conclusion affirms that integrating these assessment methods creates a more dynamic, reflective, and effective language learning environment.